SAT0342 Features of Orbital Inflammatory Disease and Response To Immunosuppressive Therapy. (15th July 2016) - Casian, A.; Sangle (joint first author), S.; Malaiya, R.; Lutalo, P.; Nel, L.; Menon, B.; Verma, H.; Stanford, M.; D'Cruz, D.
Abstract : Objectives: To characterize a single centre retrospective case series of patients with infra-orbital inflammatory masses with autoimmune disease including granulomatosis with polyangiitis (GPA) (formerly Wegener's granulomatosis), eGPA (eosinophillic granulomatosis with polyangiitis) or Immunoglobulin G4 (IgG4) related disease (IgG4-RD). Methods: We identified 30 patients with infra-orbital inflammation on MRI imaging. Clinical and laboratory data was collected from electronic clinical records. Comprehensive Diagnostic Criteria were used for IgG4-RD and Chapel Hill criteria for GPA and eGPA. Statistical analysis was performed by GraphPad software; continuous variables were compared between IgG4-RD and GPA groups using non-parametric Mann-Whitney test and categorical variables were compared by Fisher's exact test. Results: The study included 21 Caucasian, 6 Asian and 3 patients of African descent. There were 19 female and 11 male patients. The median age of the patients was 44 years (range 29–76). 13 patients were diagnosed with GPA, 1 with eosinophillic granulomatosis with polyangitis 9eGPA), 11 patients had IgG-RD, 1 patient with lymphoma, 2 other vasculitis, 1 IgA dacryoadenitis, 1 non-specific granuloma. 7/12 patients with IgG4-RD had isolated infra-orbital masses whereas all 14 GPA patients suffered extra-ocular manifestations (p=0.01), usually sino-nasal or pulmonary. 11/14 GPA patients had positive ANCA vs 2/12 patients with Ig4-RD (p=0.04). IgG4 level was elevated pre-treatment in IgG4 RD patients (median 2.46 g/l (range 1.2–23.7)) and dropped to 1.25 g/l (range 0.37–10.4) after therapy; immunoglobulin subclasses were not checked routinely in GPA. All 12 patients with IgG4-RD underwent diagnostic orbital biopsy vs 3/14 GPA (p=0.0001). All 30 patients were treated with corticosteroids (used alone in 3/12 IgG4-RD patients). The median number of DMARDs ever used to treat GPA was 3 vs 1 DMARD for IgG4-RD (p=0.001). Rituximab was effectively administered to 10/14 GPA patients vs 3/12 IgG4-RD (p=0.04), is planned for 2 further IgG4-RD patients and approval was refused for 1 case. Surgical debulking was undertaken in 6/12 IgG4-RD vs 1/14 GPA (p=0.03). All 40 patients had subsequent MRI to assess response to therapy. Conclusions: IgG4-RD is an important differential diagnosis of infra-orbital inflammation, especially if ANCA is negative. Unlike GPA that was associated with extra-ocular manifestations in all patients, IgG4-RD was more likely to present with isolated orbital inflammation and to require biopsy or surgical debulking as the diagnosis was initially uncertain. Treatment with corticosteroids +/− DMARDs was effective. Rituximab can specifically deplete the pool of autoreactive B lymphocytes producing IgG4 and future systematic studies are required to establish the optimum therapeutic strategy. Disclosure of Interest: None declared